Analisa Pengujian Kualitas Citra Steganografi Dengan Pendekatan Parameter PSNR Dan MSE - Dimas Yoga Prayuda (Universitas Harapan Medan, 2021)
This study discusses the analysis of steganography image quality testing with the PSNR and MSE parameter approaches. The purpose of this study is to insert messages into the cover image and extract messages from within the stego image, to determine the resilience of the results of inserting messages into the image using the PSNR and MSE approaches, and to design a steganography application and to test the durability of the stego image quality. in this study to analyze the quality of steganographic image testing using the LSB (least significant bit) method. LSB method has several criteria, namely recovery, videlity and robustness. the test results are strengthened by looking at the MSE (mean square error) and PSNR (peak signal to noise ratio) values. PSNR has a standard value for each cover image that is inserted a message, which is >30db (decibels), while the smaller the MSE, the better. the results of the study indicate that the steganography test criteria for the recovery criteria have been met, the videlity criteria have been met because the MSE value produced is quite small while the PSNR value is large and has met the threshold of >30 db, while testing the steganography criteria on the robustness criteria which is done by changing the contrast value of the stego image, performing image operations and image crop operations is not successful because the message content is damaged.